THE ROLE OF WORK MOTIVATION AND ORGANIZATIONAL JUSTICE IN EMPLOYEE STRESS: A CROSS-SECTIONAL STUDY - Nguyen, Phuoc-Thien; Nguyen-Le, Lam-Tuyen; Duong-Vo, Thien-Ly; Tran-Thien, Gia-Phuoc; Tran-Chi, Vinh-Long (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Job stress has become an increasingly important concern in the rapidly expanding food and beverage industry in Vietnam, where demanding service conditions and intensive workloads place employees at high psychological risk. Limited empirical research has examined how individual motivation and organizational fairness shape stress levels in this sector. The study analyzes the relationships among work motivation, distributive justice, career orientation, and job stress to clarify the factors that may influence employees’ stress experiences. A cross-sectional design was used, and survey data were collected from 123 employees working in food and beverage businesses in southern Vietnam. Standardized scales were applied to measure intrinsic and extrinsic motivation, distributive justice, career orientation, and job stress. Descriptive statistics, one-way analysis of variance, correlation analysis, and multiple linear regression were performed to evaluate statistical associations. The results reveal that amotivation shows a strong positive relationship with job stress (β = 0.528, p < 0.001). Introjected regulation (β = −0.193, p < 0.05) and distributive justice (β = −0.166, p < 0.05) are negatively related to stress scores. Employees working fewer than seven hours per day report significantly lower levels of identified regulation and integrated regulation compared with those working longer hours. No significant direct effect of career orientation on job stress is observed. The major findings indicate that motivation profiles and fairness perceptions account for a meaningful proportion of variance in job stress, whereas career orientation contributes no measurable direct influence. These results provide quantitative evidence that psychological and organizational conditions jointly shape stress outcomes in food and beverage workplaces.